Catalytic partial oxidation reformation of diesel, gasoline, and natural gas for use in low temperature combustion engines. (15th June 2019) - Hariharan, Deivanayagam; Yang, Ruinan; Zhou, Yingcong; Gainey, Brian; Mamalis, Sotirios; Smith, Robyn E.; Lugo-Pimentel, Michael A.; Castaldi, Marco J.; Gill, Rajinder; Davis, Andrew; Modroukas, Dean; Lawler, Benjamin
Abstract: Onboard reforming has relevance to both conventional and advanced combustion concepts. Most recently, onboard reforming has been proposed to enable "Single-Fuel RCCI" combustion and therefore, this paper explores catalytic partial oxidation reforming of three potential transportation-relevant fuels: gasoline, diesel, and natural gas. Reformation is performed at two pressure levels (between 15 and 60 psig) for each parent fuel for equivalence ratios ranging from 3.7 to 7.6 and the gaseous reformate mixtures are characterized with gas chromatography. The percentage of diesel oxidized during reformation is similar across all of the equivalence ratios. However, the percentage of gasoline and natural gas oxidized during reformation decreased with increasing equivalence ratio. The energy released during the reformation process is also calculated and presented for each gaseous reformate fuel. The lower heating value of every reformate fuel is lower than 20% of their respective parent fuel, due to the high concentration of inert gases (mostly nitrogen) in the reformate fuel mixtures. Two reformed fuels for each parent fuel were then selected to study their autoignition characteristics using HCCI combustion on a Co-operative Fuel Research (CFR) engine. The equivalence ratio is maintained at 0.31 and the combustion phasing was held constant by varying the intake temperature. Although the equivalence ratio is constant, the input energy from the different reformate fuels is not constant due to the component concentrations in the fuel. The gaseous reformate fuels are then compared to gasoline, natural gas, and the primary reference fuels in HCCI to determine an effective Primary Reference Fuel (PRF) number or effective octane rating for each gaseous reformate fuel. The effective octane rating for the gaseous reformate fuels fell slightly above the PRF number scale at an effective octane number of ∼110.